Constructing Piano Performance Teaching Guidebook from Traditional Folk Song of Hei long jiang Province for Students Major in Piano Performance at Jiamusi University, The People’s Republic of China - Xi, Ai; Sondhiratna , Thanyawat; Pongvatnanusorn, Panravee (Journal of Roi Kaensarn Academi, 2024)
The significance of inheriting, protecting and developing the folk songs of Heilongjiang ethnic minorities with the rapid economic development, the cultural traditions of the ethnic minorities have been strongly impacted and even slowly disappearing. The purposes of the study were (1) to study piano performance teaching of Heilongjiang traditional folk songs. (2) To construct the teaching guide of Heilongjiang traditional folk song piano performance for the piano major of Jiamusi University. (3) To experiment the teaching of piano students of Jiamusi University School of Music playing by using "Heilongjiang Traditional Folk Song Piano Performance Teaching Guide". (4) To evaluate the results of teaching by using "Heilongjiang Traditional folk song piano performance teaching Guide". The research methodology was mixed method which conducted by qualitative research, and quantitative research. The researcher interview 3 key informants and experiment the guidebook with the sample of 27 students majoring in music performance piano, School of Music, Jiamusi University. The research results are as follows. The guide includes an introduction to piano works adapted from Heilongjiang folk songs, as well as detailed explanations of basic exercises, teaching methods, sheet music and teaching plans related to performance courses. The teaching plan of this course is to teach 19 piano works adapted from Heilongjiang folk songs. Each class is divided into four parts for analysis and explanation: background of the work, introduction of the work, analysis of playing skills, and explanation of music style. Each student has a different problem with the assignment, so in the above study, the researchers summarized five teaching methods related to the teaching focus and difficulty. In the course of teaching, different problems can be explained.